Komposisi Jenis Bulu Babi (Kelas: Echinoidea) di Daerah Intertidal Pulau Lemukutan Kabupaten Bengkayang - Ari Hepi Yanti, Andi Ristanto, Tri Rima Setyawati, (Jurnal Protobiont, 2017)
Sea urchins belong to the class Echinoidea. This species lives in intertidal waters. This research aims to determine the species composition of sea urchins in the intertidal area of Lemukutan Island. The research was conducted in July 2015, using the transect method. Each station consisted of 3 transects with a length of 50 meters from the shore into the sea and each transect within 10 meters of the other transects. This research obtained four species consisting of three species of the genus Diadema and one species of the genus Echinotrix (Diadema antillarium, D. savignyi, D. setosum and Echinotrix calamaris). The species of sea urchins most commonly found are the species D. setosum as many as 147 individuals, while the least found were the species D. antillarium as many as five individuals.